Atlas of Skin Disorders Challenging Presentations of Common to Rare Conditions (Springer Singapore, 2018)
This book was written to assist the dermatologists and practitioners in the management of rare and challenging skin disorders. It is the most valuable collection of such skin disorders from more than 274 outstanding contributors over 4 decades in China. In this book, a comprehensive coverage of about 387 conditions are illustrated by 1215 superb images, and each is introduced with an initial summary of clinical characters. This atlas incorporates a wide range of skin disorders from the mildest and common conditions to the most severe conditions. The objective of this book is to provide readers with a clinical reference, which can be easily approachable and possesses the necessary expertise to sharpen a dermatologist's diagnostic and clinical acumen.